Missing checkerboards: an absence of competitive signal in Alnus-associated ectomycorrhizal fungal communities - Kennedy, Peter; Nguyen, Nhu H.; Cohen, Hannah; Peay, Kabir G (PeerJ PrePrints, 2014)
A number of recent studies suggest that interspecific competition plays a key role in determining the structure of ectomycorrhizal (ECM) fungal communities. Despite this growing consensus, there has been limited study of ECM fungal community dynamics in abiotically stressful environments, which are often dominated by positive rather than antagonistic interactions. In this study, we examined the ECM fungal communities associated with the host genus Alnus, which live in soils high in both nitrate and acidity. The nature of ECM fungal species interactions (i.e. antagonistic, neutral, or positive) was assessed using taxon co-occurrence and sequence abundance correlational analyses. ECM fungal communities were sampled from root tips and mesh in-growth bags in three monodominant A. rubra plots and identified using Illumina-based amplification of the ITS1 gene region. We found a total of 183 ECM fungal taxa present across the plots; 16 of which were closely related to known Alnus-associated ECM fungi. Contrary to previous studies of ECM fungal communities, taxon co-occurrence analyses on both the total and Alnus-associated ECM datasets indicated that the ECM fungal communities in this system were not structured by interspecific competition. Instead the co-occurrence patterns were consistent with either random assembly or significant positive interactions. Pair-wise correlational analyses were also more consistent with neutral or positive interactions. Taken together, our results suggest that interspecific competition does not appear to determine the structure of all ECM fungal communities and that abiotic conditions may be important in determining the specific type of interaction occurring among ECM fungi.
Keywords: competition; facilitation; species interactions; fungal ecology; next-generation sequencing